62.9k views
5 votes
Solve by factoring

{n}^(2) - 6n= 0
Please show all work!​

2 Answers

2 votes


\\ \sf\longmapsto n^2-6n=0

  • Take n common


\\ \sf\longmapsto n(n-6)=0

Now


\\ \sf\longmapsto n=0\:or \:(n-6)=0


\\ \sf\longmapsto n=0\:or \;n=6

Hence roots of the equation are 0 and 6 .

More:-

We can solve it through Quadratic formula


\boxed{\sf x=(-b\pm √(b^2-4ac))/(2a)}

User JohnyMSF
by
5.3k points
5 votes

Answer:


n=0,\\n=6

Explanation:

Given
n^2-6n=0, we can factor out an
n from each of the terms on the left side of the equation:


n(n-6)=0

Since we have two factors that multiply to zero, we can set each of them to zero and solve for
n, because zero multiplied by anything is equal to zero. Therefore, as long as either
n or
n-6 is equal to zero, the other factor can be any real number and the equation would still hold true.

Therefore, we have the following cases:


\begin{cases}n=0,\\n-6=0\end{cases}

Solving, we get:


\begin{cases}n=0, n=\boxed{0}\\n-6=0, n=\boxed{6}\end{cases}

User Stoatman
by
5.2k points